(untitled) - Singer, Charles (Oxford, 1959)
This book is based on one bearing the title "A history of scientific ideas", drafted first in 1929 and published in 1941. It underwent several revisions but the present forms is much more than a revision and rather more than a new dedition.
Keywords: Khoa học,Science,Science,Khoa học; Triết học,History,Philosophy,Lịch sử